Taxonomy of the Proisotoma complex. III. A revision of the genus Narynia (Collembola: Isotomidae) with a description of a new species from China - Huang, Cheng-Wang; Potapov, Mikhail; Gao, Yan (Zootaxa, 2010)
The three known species in the genus Narynia Martynova, Narynia setosa Martynova, Narynia andreevae Martynova in Martynova & Tshelnokov and Narynia kolimiensis Martynova are revised based on type specimens. A new species for the genus, Narynia luanae sp.n. from Northwest China, is described. An identification key to the species and the diagnosis of the genus are given.